Selective Bacteriocins: A Promising Treatment for Staphylococcus aureus Skin Infections Reveals Insights into Resistant Mutants, Vancomycin Resistance, and Cell Wall Alterations - Félix Jaumaux; Kenny Petit; Anandi Martin; Hector Rodriguez-Villalobos; Marjorie Vermeersch; David Perez-Morga; Philippe Gabant (MDPI AG, 2023)
The emergence of antibiotic-resistant S. aureus has become a major public health concern, necessitating the discovery of new antimicrobial compounds. Given that the skin microbiome plays a critical role in the host defence against pathogens, the development of therapies that target the interactions between commensal bacteria and pathogens in the skin microbiome offers a promising approach. Here, we report the discovery of two bacteriocins, cerein 7B and cerein B4080, that selectively inhibit S. aureus without affecting S. epidermidis, a commensal bacterium on the skin. Our study revealed that exposure of S. aureus to these bacteriocins resulted in mutations in the walK/R two-component system, leading to a thickening of the cell wall visible by transmission electron microscopy and subsequent decreased sensitivity to vancomycin. Our findings prompt a nuanced discussion of the potential of those bacteriocins for selective targeting of S. aureus on the skin, given the emergence of resistance and co-resistance with vancomycin. The idea put forward implies that by preserving commensal bacteria, selective compounds could limit the emergence of resistance in pathogenic cells by promoting competition with remaining commensal bacteria, ultimately reducing chronical infections and limiting the spread of antibiotic resistance.